2018
DOI: 10.1080/08856257.2018.1424783
|View full text |Cite
|
Sign up to set email alerts
|

Student voices on social exclusion in general primary schools

Abstract: Advocates of inclusive education argue that the social inclusion of students with special educational needs (SEN) increases when they are educated with typically developing peers. However, research indicates that this is not apparent for all students with SEN. Students with social, emotional and behavioural difficulties (SEBD) are often socially excluded. To understand the situation of these students, their voices should be heard. The aim of the current explorative study was to gain insight into: (1) the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
1
20
0
3
Order By: Relevance
“…The differences in the profiles within and between the situations highlight the importance of examining the preferences of each child and situation. This point is in line with the recommendations of de Leeuw et al (2018). These authors, who conducted an interview-based study with children with SEBD in grade 5 and 6, found that it was not possible to formulate a one-size-fits-all approach for resolving either social exclusion or situations of victimisation due to bullying.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The differences in the profiles within and between the situations highlight the importance of examining the preferences of each child and situation. This point is in line with the recommendations of de Leeuw et al (2018). These authors, who conducted an interview-based study with children with SEBD in grade 5 and 6, found that it was not possible to formulate a one-size-fits-all approach for resolving either social exclusion or situations of victimisation due to bullying.…”
Section: Discussionsupporting
confidence: 79%
“…The needs and preferred approaches of individual children and situations are likely to vary significantly. Children could prefer different approaches, but due to circumstances apply approaches that they like less (de Leeuw et al, 2018). Future research, including longitudinal studies of preferences and applied strategies are expected to reveal differences attributed to the situational context of the social problem and to the child-related context (Green et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive attributions like 'People hate me' make the victims to resolve bullying situation by changing school, but they still remain at high risk of new victimization experiences (Smokowski & Evans, 2019). Moreover, students applied externalizing approaches in order to resolve these situation, which usually included approaching the stressor (De Leeuw et al, 2018). Usually, the victims lack emotion regulation skills and therefore, reactive aggression is an expected outcome, which is negatively correlated with sadness (Giménez Gualdo, Hunter, Durkin, Arnaiz, & Maquilón, 2015).…”
Section: Bullying Victimmentioning
confidence: 99%
“…For example 'There were two boys who would call me names and say that I looked like a girl. That hurt me so much that I would see a red haze and I would punch and kick them' (De Leeuw et al, 2018) The victim is victimized as he is noticed by his/her bully, for example, being in a playground or being online on social media. Therefore, the input states of the model are activated already (ws s and es b = 1), which activates the preparation state of the approach action (ps app : purple with asterisks) after the sensory (ss s,b ) and representation states (srs s,b ).…”
Section: Approach Strategymentioning
confidence: 99%
See 1 more Smart Citation